The Role of Influencer Marketing to Improve Organizational Performance and its Impact on Purchasing Decisions - Cucu Hodijah; Amalia Juliana Monika Intan; Rika Solihah; Santi Maria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the role of influencer marketing to improve organizational performance and its impact on consumer purchasing decisions. This study uses a descriptive verification approach, a sample of 131 SME owners using incidental techniques. Data analysis used SEM with Amos software version 22. The primary data of this study was obtained from a questionnaire. While secondary data obtained through notes and publications as well as literature study.The results showed that the role of influencers had a positive and significant effect on organizational performance and purchasing decisions, and the role of influencers had a positive effect on organizational performance through mediation of purchasing decisions. This study is proposed to determine the aspects of the role of influencer marketing related to organizational performance in SMEs in the city of Bandung and also emphasizes aspects of competitive competence that have an impact on performance, especially in SMEs.